Comparison of Survival, Productivity, Movements, and Habitat Use of Pre-Season Released Quail on Wild Northern Bobwhites on Groton Plantation, South Carolina - Derek A. Eggert; Brad S. Mueller; Lamar Robinette; Shane D. Wellendorf (National Quail Symposium Proceedings, 2017)
To understand the effects of a pre-season release operation (liberating pen-raised quail for hunter harvest) on native quail (Colinus virginianus) populations, we developed studies to assess population demographics and movements of three treatment groups (wild, pen, and wild/pen quail) on Groton Plantation, Allendale County, South Carolina. Two isolated study sites were selected: a site with only wild quail (control) and a site with both wild quail and pen-raised quail released each September (treatment). We radio-tagged wild (n = 306) and pen-raised (n = 330) quail during 1996 and 1997, for monitoring various demographic parameters, including body weight, survival rate, home range, habitat use, linear dispersal, and hunting susceptibility. Based on data from this study, the release of pen-raised quail affected the behavioral characteristics of wild quail and possibly physical characteristics such as body weight. Individual body weight measurements indicated that a higher percentage of wild/pen quail weighing more than wild quail during both years (March 1996 and 1997). While these data are not direct measurements of introgression, reproductive success of pen-raised quail was observed during two consecutive breeding seasons (44% and 22%). Behavioral characteristics such as home range size, habitat-use, and linear dispersal were different between wild/pen and wild control quail during specific periods (i.e., season and year) potentially causing lower survival rates (0.077 ± 0.074) during the 1997 overwinter season and increased hunter susceptibility. While the pre-season release of pen-raised quail can produce economically efficient hunting, negative impacts on native quail population may occur.
Keywords: Colinus virginianus; northern bobwhite; pen-raised quail; pre-season release; South Carolina